Studi Literatur: Analisa Perbandingan Teori Tentang Tingkat Keamanan Antar Algoritma Simetris - Bhaskara, I Made Adi; Ariawan, Made Pasek Agus; Peling, Ida Bagus Adisimakrisna; Prayudha, I Putu Astya (Jurnal Bangkit Indonesia, 2024)
Data security has become a critical issue in the digital age, and cryptographic algorithms play a vital role in preserving information confidentiality. Symmetric algorithms offer convenience and speed, but choosing the right algorithm is crucial to ensuring an adequate level of security. Disciplines of cryptography is generally known, there are two categories of a data encryption and decryption algorithm one of which is a symmetric algorithm. Symmetric algorithms are widely used in the encryption of the data so that new theories are emerging. Types of symmetric algorithms are various algorithms such as DES algorithm, AES or Rijndael algorithm, 3DES algorithm and others. Along with the many theories of symmetric algorithms are used in the discipline cryptography, the security of an algorithm with other algorithms need to be compared to find the most appropriate against attack. Based on this literature study results obtained that the AES algorithm is the most secure algorithm compared to DES and 3DES.